Эффект отражения мелкодисперсных испаряющихся капель встречным потоком газа - Ольшанский, В. П.; Ольшанский, Станислав Васильевич (НТУ "ХПИ", 2006)
The movement of a drop is considered which evaporates, as material point of variable weight. In the assumption, that the force of aerodynamic interaction of a drop with gas environment is proportional to a square of speed of a flow, the approached analytical decisions of the nonlinear differential equations of movement are received, in special functions. The effect of reflection of a drop is investigated, that is change of her direction movement, counter gas flow is exacter
Keywords: цилиндр двигателя внутреннего сгорания; скорость испарения; поток газа; дальность полета капли